The impact of transient interplanetary structures on Solar Energetic Particles - Κωλέττη, Μυρτώ (Πανεπιστήμιο Πελοποννήσου, 2020)
Solar energetic particles (SEP) are a significant component of space weather, due to their strong impact on terrestrial and space human activity. They constitute an important field of research and the better understanding of the physical processes that dominate them is key to the advancement of space weather forecasting tools. The goal of this thesis is to investigate the impact of transient interplanetary structures on SEP intensities. Specifically, we focus on the effect of the specific interplanetary magnetic field (IMF) configuration determined by the position of one or more interplanetary coronal mass ejections (ICMEs) at the time of the maximum proton intensity, based on in-situ measurements. For this purpose, a catalogue of 98 western SEP events is compiled. The SEP events are classified to 6 classes, based on the location of one or more ICMEs with respect to the observer at the time of the maximum proton intensity. Firstly, we confirm that, SEP events associated with more intense solar conditions, statistically reach higher proton intensities. Moreover, events that occur during periods that multiple ICMEs are present in the interplanetary space, are expected to reach higher intensities, as well. Generally, SEP events are most likely to be associated with one or more ICMEs. Specifically, the most common events are those that occur when the Earth is immersed within an ICME. We also conclude that, the location of one or more ICMEs at the time of the maximum proton intensity is a significant factor affecting the observed proton intensity. More specifically, events that occur when Earth is immersed within an ICME or after an ICME has passed Earth, are statistically associated with the highest proton intensities. Specifically, for events observed after a preceding ICME has passed Earth, the observed proton intensity statistically increases with the speed of the ICME. Events that occur within the standard solar wind, in the sheath region of an ICME or shortly before an ICME passes Earth, reach lower intensities. Lastly, the magnetic configuration within an ICME is also an important factor. For given solar conditions, the proton intensity of a SEP event immersed within an ICME with a magnetic cloud (MC) configuration is expected to reach lower intensities, compared to events immersed within ICMEs without an MC configuration.
Η επίδραση των παροδικών διαπλανητικών δομών στα ηλιακά ενεργειακά σωματίδια
Μ.Δ.Ε. 75
Keywords: solar energetic particles; SEP; solar flare; coronal mass ejection; magnetic cloud; solar wind